The Contribution of Social Media, E-WOM On Brand Images and Purchase Intention - Arliyarini Erlikamila Yanti; Tatik Suryani (IPTEK Journal of Proceedings Series, 2020)
Recently, many companies used social media (Facebook and Instagram) for promoting their product and services. Is social media has a significant contribution on marketing performance? Many research focus on sales as marketing performance, less of the focus on other marketing performance such as: E-WOM, brand images and purchase intention. The specific focus of the research (1) to examine the influence of social media (Facebook and Instagram) toward E-WOM, (2) to examine the influence of E-WOM towards brand image (3) to examine the influence of brand image toward purchase intention (4) to examine the influence of E-WOM toward purchase intention and (5) to examine is brand image mediating the influence of social media and E-WOM toward purchase intention. This research is qualitative design based on theoretical review and supported by many previous research. The basic concept of theory is about social media quality, E-WOM, Brand Image, and Purchase Intention.The proposition as the result studies can be investigated empirically.